Model Parenting Untuk Generasi Z Berdasarkan Konsep Al Qur’an Surat Luqman Ayat 13-19 - Rohmah, Faiqotur; Mustajab, Mustajab (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The purpose of this research is to find out the parenting model based on the Qur’anic concept at Luqman’s chapter verses 13th to 19th and it’s relevance for Z Generation. This research based on Library research, because the kind of this statement is analysis. This study analyzes Luqman’s chapter verses 13th to 19th with the main points of the language in the concept of parenting. The data collection technique used by the author in this study was to find and collecting the books which are sources of primary and secondary information, namely the Al-Qur'an as the primary source and other books as secondary sources. The data analysis technique used in this research is a descriptive analysis. Where was included as a research method in which the sources are collected analyzed then interpreted critically, then presented systematically and accompanied by related explanations to make it easier to understand and draw conclusions. The study’s it was concluded that there were several parenting points contained in Luqman's chapter in the Qur’an, as Luqmanul Hakim had bequeathed to his son and it’s relevance to Z Generation education